Estimating the Economic Threshold Levels of Spodoptera frugiperda through Larval Damage and Adult Moth Trap Catches in Andhra Pradesh, India - B. L. Manisha; Venkateswarlu, N. C.; Chalam, M. S. V.; Devi, R. Sarada Jayalakshmi; Raman, B.; Murthy; Manjula, K.; Rajasri, M.; Kumar, K. Sunil; Kumar, N. Jashwanth; et al. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during kharif (June–September, 2022) in the Rayalseema region of Kurnool, Chittoor, Kadapa and Ananthapuramu districts, Andhra Pradesh, India to determine the percentage of leaf and cob damage caused by Fall armyworm. The roving surveys were carried out throughout the crop’s vegetative (7 to 45 DAS) and reproductive (50 to 70 DAS) stages in the major Maize growing areas. The findings of the roving survey on the incidence of FAW during the kharif (June–September, 2022) showed that, of the districts surveyed, Kurnool (82.62%) and Chittoor (71.20%) recorded the highest percentage of leaf damage, followed by Kadapa (65.14%) and Ananthapuramu (52.82%) during vegetative stage. The districts with the highest percentage of cob damage during the reproductive stage were Chittoor (67.99%) and Kurnool (58.88%), followed by Kadapa (54.21%) and Ananthapuramu (53.21%), Through these surveys the extent of damage in each stage of Maize can be assessed. Using pheromone traps to study population dynamics of FAW is a great way to keep a watch on pest populations which not only improves early detection but also helps to determine the ETL levels of adults as a forewarning signal to the Maize cultivators. The Phermone trap catches during kharif, 2022 showed that at 28 days after planting (V5, V6, and V7 stages of Maize), Chandragiri recorded the highest trap catches for the entire season, with 70.99 moths trap-1 week-1 followed by Narayanavanam at 21 DAS with 73.11 moths trap-1 week-1 which exceeded the ETL level.